Novel use of 4D-CTA in imaging of intranidal aneurysms in an acutely ruptured arteriovenous malformation: is this the way forward?. (15th July 2015) - Chandran, Arun; Radon, Mark; Biswas, Shubhabrata; Das, Kumar; Puthuran, Mani; Nahser, Hans
Abstract : Ruptured arteriovenous malformation (AVM) is a frequent cause of intracranial hemorrhage. The presence of associated aneurysms, especially intranidal aneurysms, is considered to increase the risk of re-hemorrhage. We present two cases where an intranidal aneurysm was demonstrated on four-dimensional CT angiography (time-resolved CT angiography) (4D-CTA). These features were confirmed by digital subtraction angiography (catheter arterial angiogram). This is the first report of an intranidal aneurysm demonstrated by 4D-CTA. 4D-CTA can offer a comprehensive evaluation of the angioarchitecture and flow dynamics of an AVM for appropriate classification and management.